2017
DOI: 10.1089/aivt.2016.0037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytotoxic, Oxidative, and Pro-Inflammatory Effects of Aqueous Cigarette Smoke Extract on Human Monocytes: A Potential Model System for Assessment of Next-Generation Tobacco and Nicotine Products

Abstract: Tobacco smoking is a risk factor for the development of atherosclerosis. One strategy to reduce the harmful side effects of tobacco smoking is the development of next-generation tobacco and nicotine products. A crucial step in the development of atherosclerosis is the activation and adhesion of monocytes. Remarkably, little is known about the direct effects of cigarette smoking on monocytes. In this study, we developed methods to determine the detrimental effects of aqueous cigarette smoke extract (CSEaq) from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Several studies indicated an atherosclerosis-related gene expression profile of endothelial cells as well as of monocytes in the presence of the main behavioural risk factor smoking [ 3 , 34 , 41 , 73 , 77 ]. Independent stimulation with aqueous smoke extract (AqE) of conventional reference cigarettes (3R4F) revealed cytotoxic, oxidative, and pro-inflammatory effects on monocytes, shown in an own previous study [ 9 ].…”
Section: Introductionmentioning
confidence: 91%
“…Several studies indicated an atherosclerosis-related gene expression profile of endothelial cells as well as of monocytes in the presence of the main behavioural risk factor smoking [ 3 , 34 , 41 , 73 , 77 ]. Independent stimulation with aqueous smoke extract (AqE) of conventional reference cigarettes (3R4F) revealed cytotoxic, oxidative, and pro-inflammatory effects on monocytes, shown in an own previous study [ 9 ].…”
Section: Introductionmentioning
confidence: 91%
“…These factors were related to oxidative stress and inflammation mechanisms, especially cigarette smoke, which plays a significant role in CVD development. 3–6 …”
Section: Introductionmentioning
confidence: 99%
“…These factors were related to oxidative stress and inflammation mechanisms, especially cigarette smoke, which plays a significant role in CVD development. [3][4][5][6] Smoking behaviour is a common habit in many countries. Indonesia is ranked third with the highest number of smokers in the world (9.91 million), after China (26.5 million) and India (19.8 million).…”
Section: Introductionmentioning
confidence: 99%
“…A cigarette smoke aqueous test matrix consists of one or more cigarettes smoked into a specified volume of solution and the resulting aqueous soluble fraction of the cigarette smoke (AqE) is diluted and applied to the cell surface. Studies have used multiple methods not fully described to allow replication [ 7 , 10 , 12 , 13 ]. For instance, the puffing regime is not always specified, the capture solutions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Smoke-induced oxidative stress has been linked to chronic obstructive pulmonary disease [ 13 , 17 , 23 ] associated with impaired antioxidant defences and characterised by an accumulation of oxidised glutathione in the lungs of smokers. In this study, the effects of pro-oxidant smoke-derived chemicals in cigarette smoke (partitioned between the particulate and vapour phase) were investigated by use of AqE.…”
Section: Introductionmentioning
confidence: 99%